RANCANG BANGUN DAN UJI KINERJA MESIN PENYARING SISTEM GETAR UNTUK MEMISAHKAN BIJI DAN KULIT HANJELI HASIL PROSES PENGUPASAN - Asep Yusuf; Wahyu K Sugandi; Desi Purnamasari (The University of Lampung, 2021)
Hanjeli (Coixlacryma-jobiL.) is a cereal plant which has potential in producing carbohydrate. The high nutrient content of this plant has not been utilized optimally. In Indonesia, most of the hanjeli seed peeling processes are still using the manual way (pounding), so after the peeling process we have to do seeds and peel separating process. The purpose of this research is to devise a seed and peel filter machine occupied the results of the peeling process with vibrating screen which have been adjusted for the characteristic of hanjeli seeds. The method used in this research is engineering process, which is an activity to devise a hanjeli filter machine. The result of this research was the machine which has been designed with hopper, framework, filter unit, activator, seeds outlet, husk outlet and crank shaft as the main components. The main dimensions of the machine were 1340 mm long, 610 mm wide, 1000 mm high, the machine’s actual capacity was 29.024kg/h and the activator is 0.5 HP. The results of the hanjeli filter engine test are: the actual engine capacity is 29.024 kg / hour, the engine efficiency is 38.7%, the pulley rotation speed is 305 rpm, the electric motor power is 0.138 kW, and the noise level is 62.78 dB. Keywords: designing, hanjeli seed, hanjeli peel, performance test, vibrating screen